Rosencrantz and Guildenstern are dead - Stoppard, Tom; Popkin, Henry (Grove Press, 1967., 1967)
Alvin Theatre, David Merrick, by arrangement with The National Theatre of Great Britain, presents "Rosencrantz and Guildenstern are Dead," by Tom Stoppard, directed by Derek Goldby, associate director Claude Chagrin, scenery and costumes by Desmond Heeley, lighting by Richard Pilbrow, music by Marc Wilkinson, associate producer Samuel Liff, with Brian Murray, John Wood, Paul Hecht, Alexander Courtney, Noel Craig, B.J. DeSimone, Ralph Drischell, Roger Hamilton, Michael Holmes, Carl Jocobs, Roger Kemp, Dino Laudicina, Roy Lozano, Patricia McAneny, Anne Meacham, Douglas Norwick.
Alvin Theatre, December 1967.
"Playbill. Volume 4. December 1967. Number 12"--p. [3].
Title devised by Library staff.
Cast: Brian Murray, John Wood, Paul Hecht, Douglas Norwick, Roger Kemp, Dino Laudicina, B.J. De Simone, Roy Lozano, Noel Craig, Patricia McAneny, Roger Hamilton, Anne Meacham, Ralph Drischell, Alexander Courtney, Carl Jacobs, Michael Holmes, Walter Beery, Stephen Bernstein, Gaetano Bongiovanni, Margaret Braidwood, Esther Buffler, Elizabeth Eis, Elizabeth Franz, William Grannell, John Handy, Mary Hara, Edward Marshall, Ted Pezzulo. Musicians: Bruce Levine, Bernard Karl, Jack Knitzer, Don Arol.
ENH
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: Stoppard, Tom -- Criticism and interpretation; Stoppard, Tom -- Stage history; English literature; Theater programs -- New York (State) -- New York; Theater programs -- 1967.